Defining cultural competence: a practical framework for addressing racial/ethnic disparities in health and health care. - Betancourt, Joseph R. (Association of Schools of Public Health, 2003)
OBJECTIVES: Racial/ethnic disparities in health in the U.S. have been well described. The field of "cultural competence" has emerged as one strategy to address these disparities. Based on a review of the relevant literature, the authors develop a definition of cultural competence, identify key components for intervention, and describe a practical framework for implementation of measures to address racial/ethnic disparities in health and health care. METHODS: The authors conducted a literature review of academic, foundation, and government publications focusing on sociocultural barriers to care, the level of the health care system at which a given barrier occurs, and cultural competence efforts that address these barriers. RESULTS: Sociocultural barriers to care were identified at the organizational (leadership/workforce), structural (processes of care), and clinical (provider-patient encounter) levels. A framework of cultural competence interventions--including minority recruitment into the health professions, development of interpreter services and language-appropriate health educational materials, and provider education on cross-cultural issues--emerged to categorize strategies to address racial/ethnic disparities in health and health care. CONCLUSIONS: Demographic changes anticipated over the next decade magnify the importance of addressing racial/ethnic disparities in health and health care. A framework of organizational, structural, and clinical cultural competence interventions can facilitate the elimination of these disparities and improve care for all Americans.